A new offloading paradigm:vehicular edge task offloading based on parked vehicles relay - Peiyang DONG; Junhui ZHAO; Dan ZOU; Xiaoke SUN (Dianxin kexue)
Vehicular edge computing (VEC) is a key technology that can realize low latency and high reliability in vehicular network.VEC can solve the problem of insufficient computing of vehicle terminals,and reduce the communication service delay of vehicular network,avoiding a large amount of waste of free resources in parked vehicles on the road.A task offloading scheme based on parked vehicles relay was proposed,which could reduce the delay in vehicles’ communication process into the millisecond level by rationally deploying the edge server and introducing the cooperative relay technology.Numerical results indicate that compared to direct V2I offloading model,the communication delay can be reduced by 20% in the parked vehicle relay transmission.